2018
DOI: 10.20517/2394-5079.2018.57
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and viral risk factors for hepatocellular carcinoma in the Eastern Mediterranean countries

Abstract: Given the high prevalence of viral hepatitis in the Eastern Mediterranean countries, hepatitis B and C infections are the major causes of hepatocellular carcinoma (HCC) in the region. Most cases are associated with cirrhosis related to hepatitis B or C infection. Environmental, host genetic and viral factors can affect the risk of HCC in patients with hepatitis B and C infection. Understanding the epidemiology and viral risk factors in the region provides the implementation of strategies for prevention and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 63 publications
1
23
1
1
Order By: Relevance
“…307 (69.7%) patients were tested positive for hepatitis C virus (HCV) while HBV was present in 67 patients (15.2%) and 4 patients (0.9%) were considered chronic alcoholics [26]. According to new data about HCC etiologies, HBV contributes in 31% of HCC cases, while HCV, alcohol, and other factors contribute in 36, 14, and 19%, to HCC development, respectively [28].…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…307 (69.7%) patients were tested positive for hepatitis C virus (HCV) while HBV was present in 67 patients (15.2%) and 4 patients (0.9%) were considered chronic alcoholics [26]. According to new data about HCC etiologies, HBV contributes in 31% of HCC cases, while HCV, alcohol, and other factors contribute in 36, 14, and 19%, to HCC development, respectively [28].…”
Section: Preventionmentioning
confidence: 99%
“…Patients with HBV-related HCC, aged between 51 and 90 years, revealed that the male/female ratio was 9.33 [43]. Recent data showed that HBV, HCV, alcohol, and other factors contribute to HCC in 20, 44, 18, and 18%, respectively [28]. To overcome HBV and HCC problems in health institution, Tunisia provides vaccination to health professionals [44].…”
Section: Preventionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) is an epidemic that affected about 10-15% of people in Egypt (Elghazaly et al, 2018). Hepatocellular carcinoma related to chronic hepatitis C constitutes about 63% of cases and about 90% of them were of genotype 4 HCV infection (Yapali and Tozun, 2018). This leads to late discovery of HCC with and involved in the development of HCC (Li et al, 2014;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…HCC globally ranks fifth for incidence and third for mortality among all malignant tumors. China is the most severely affected by liver cancer, which accounts for more than 50% of all HCC cases and 55% of liver cancer deaths [2]. Although some progress has been made in exploring the pathological mechanisms and interventions of chronic liver diseases, there are still no effective biomarkers for the prediction and prevention of the progression of chronic liver diseases.…”
Section: Introductionmentioning
confidence: 99%